PROSES PENETRASI SOSIAL PADA PEREMPUAN DALAM MEMBANGUN HUBUNGAN ROMANTIS MELALUI APLIKASI KENCAN ONLINE BUMBLE DI SURABAYA - Perdana, M. Wildan Galih (Universitas Negeri Surabaya, 2022)
The creation of an application to find a partner in the all- online makes users without meeting in person or face to face in building a relationship, which in the online dating phenomenon many people claim to have got their partner to the level of marriage through online dating applications, but there are also those who get unwanted treatment when using the application such as harassment, to violence. One of the online focused on in this research is bumble. The difference between bumble and other applications is that women are required to start a chat with their match partner first, with the aim of women having control over the relationship. This study discusses the process of social penetration of women in building romantic relationships through the online dating application bumble in Surabaya. Social penetration itself is a communication process that moves from supervisory communication to intimate communication. This is the core of the discussion in this study because the communication process that is established is done online. This study uses a qualitative method by conducting interviews with informants. Based on the results of the study, there are stages of social penetration that are passed from superficial relationships to become more intimate to establishing a relationship based on commitment (dating). However, the process is not always complete, there is a possibility that a relationship may not reach the final stage or courtship. This occurs because of the process of social de-penetration, namely the process of withdrawal due to a discrepancy at a stage that is passed. Causing the relationship to step back or away, due to several unwanted factors or incompatibility by the source.